Podgorica: an Urnfield period settlement as part of the Podgorica-Dragomelj ‘twin settlement’ and an Early Iron Age cemetery - Petra Vojaković (Arheološki Vestnik, 2025)
The article presents the results of the archaeological investigations conducted at Podgorica. They revealed a settlement considered part of the Podgorica-Dragomelj ‘twin settlement’ that was located at a former streambed and extended across more than 2 ha. The clustered buildings in its centre and the metallurgical-casting activities moved to the periphery indicate a deliberate organisation of the living and work spaces of its inhabitants. The area was then reused in the Early Iron Age, when it served as a burial ground in the Hallstatt period.